Analysis of Natural and Power Plant CO2 Emissions in the Mount Amiata (Italy) Volcanic–Geothermal Area Reveals Sustainable Electricity Production at Zero Emissions - Alessandro Sbrana; Alessandro Lenzi; Marco Paci; Roberto Gambini; Michele Sbrana; Valentina Ciani; Paola Marianelli (Energies, 2021)
Geothermal energy is a key renewable energy for Italy, with an annual electric production of 6.18 TWh. The future of geothermal energy is concerned with clarity over the CO2 emissions from power plants and geological contexts where CO2 is produced naturally. The Mt. Amiata volcanic–geothermal area (AVGA) is a formidable natural laboratory for investigating the relative roles of natural degassing of CO2 and CO2 emissions from geothermal power plants (GPPs). This research is based on measuring the soil gas flux in the AVGA and comparing the diffuse volcanic soil gas emissions with the emissions from geothermal fields in operation. The natural flux of soil gas is high, independently from the occurrence of GPPs in the area, and the budget for natural diffuse gas flux is high with respect to power plant gas emissions. Furthermore, the CO2 emitted from power plants seems to reduce the amount of natural emissions because of the gas flow operated by power plants. During the GPPs’ life cycle, CO2 emissions in the atmosphere are reduced further because of the reinjection of gas-free aqueous fluids in geothermal reservoirs. Therefore, the currently operating GPPs in the AVGA produce energy at a zero-emission level.